IDENTITAS GEREJA SUKU: Konstruksi Identitas Gereja Kristen Jawa (GKJ) Margoyudan dalam Pelayanan Sosial Gereja di Surakarta - Tampake, Tony; Utomo, Setyo Budi (Universitas Kristen Satya Wacana, 2019)
This article discusses the identity of the church Pasamuwan Kristen (community members) of Gereja Kristen Jawa/Java Christian Church (GKJ) Margoyudan, Surakarta, Central Java. Pasamuan Kristen GKJ Margoyudan’s identity construction is based on two factors: internal identity and external identity. By employing documents/literature review and in-depth interviews, this research found that the construction of internal identities of Pasamuan Kristen GKJ Margoyudan was built from the long history of Zending Missionary’s role from the Netherlands. The Zending Missionary had delivered the first identity of GKJ Margoyudan as a church which has characteristic of Javanese fellowship but still following many agreements of European social identity, Javanese culture domination as the main identity, and the church building as community solidarity identity. From the external side, the support came from synod of GKJ as the center of evangelism and the government, especially Central Java government. Synod of GKJ and the government support the church community to preserve Javanese culture through Javanese songs, Javanese language, and other related culture activities. They also transformed the church building into a cultural heritage in order to assimilate it with the social identity. The research found a conclusion that stronger acceptance from others to GKJ Margoyudan is partly because of the social role of the church in education and health since long ago. GKJ Margoyudan is accepted in the wider community as an assimilationist identity.